Polymer-fiber random lasers based on pumping radiation effect. (21st August 2019) - Chen, Xianxian; Xie, Kang; Zhang, Xiaojuan; Xie, Zhendong; Ma, Jiajun; Wen, Jianxiang; Chen, Jingjing; Zhang, Junxi; Cheng, Xusheng; Hu, Zhijia
Abstract: In this study, we coated laser dye-doped polymethyl methacrylate on the surface of a bare polymer optical fiber (POF) to fabricate new POFs. Coherent random lasers are obtained for the gain POFs under the pump of a 532 nm laser. The mechanism for the random lasers is based on the refractive index heterogeneity scattering of the coating gain polymer. The variations of random lasers with different coating thicknesses and POF lengths under radiation pumping mode have been investigated. One important finding from our experiment is that dye-doped POF exhibits good photostability and self-healing properties. In addition, polymer-fiber random lasers as a sensor are researched in different concentrations of solutions. The intensity of the random lasers increases with the increase of the content of the surrounding ethanol solution due to swollen effect of the POF with a large gain length.